1985
DOI: 10.1007/bf02534402
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of positional distribution of fatty acids in palm oil by13C NMR spectroscopy

Abstract: The13C NMR spectrum of the carbonyl carbons of the acyl groups of triacylglycerols of palm oil has been shown to give the composition of saturated, oleic and linoleic acyl groups at the 1,3‐positions and at the 2‐position of the glycerol moiety. Except for the lack of differentiation of the saturated fatty acids, the13C NMR technique provides the same information as the tedious enzymatic hydrolysis cum fatty acid analysis. The carbonyl carbon of the linolenic acyl group (18∶3,[cis, cis, cis]‐9, 12, 15) has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 13 publications
0
40
2
2
Order By: Relevance
“…The general rules that apply to the resonances of triacylglycerols in vegetable oils and animal fats and the assignments reported in the literature (1,3,4,9,14,15) on similar systems suggest that these peaks belong to monoenoic cis-11 fatty acids, mainly in sn-1,3 position. This hypothesis was verified by the addition of a small amount of eicosenoic triacylglycerol to one of the olive oil samples.…”
Section: Resultsmentioning
confidence: 91%
“…The general rules that apply to the resonances of triacylglycerols in vegetable oils and animal fats and the assignments reported in the literature (1,3,4,9,14,15) on similar systems suggest that these peaks belong to monoenoic cis-11 fatty acids, mainly in sn-1,3 position. This hypothesis was verified by the addition of a small amount of eicosenoic triacylglycerol to one of the olive oil samples.…”
Section: Resultsmentioning
confidence: 91%
“…Liquid state NMR has been used in many studies to analyze lipids (Gunstone, 1991a(Gunstone, ,b, 1993(Gunstone, , 1994Lie Ken Jie and Mustafa, 1997;Mannina et al, 1999;Meneses and Glonek, 1988;Ng, 1985;Sacchi et al, 1997;Schiller et al, 2007;Sotirhos et al, 1986;Vlahov, 1996;Vlahov and Angelo, 1996;Vlahov et al, 2002). There have also been studies published for the application of liquid state NMR to evaluate algal lipid extracts (Boyle-Roden et al, 2003;Meneses et al, 1993;Pollesello et al, 1992Pollesello et al, , 1993 and ''bio-oil'' produced from the liquefaction of algae (Zou et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…The 13 C NMR spectral analysis of the carbonyl carbon atoms of the acyl groups of triacylglycerols of palm oil allowed the composition of saturated, oleic, and linoleic acyl groups at the 1,3-position and at the 2-position of the glycerol moiety to be established. The report indicated that, except for the lack of differentiation of the saturated fatty acids, the 13 C NMR technique provided the same information as the tedious enzymatic hydrolysis cum fatty acid analysis (88). The chemical shift difference of the olefinic carbon atoms in the fatty acid chain of triacylglycerols in palm oil was found to be characteristic of the chain's glycerol position and can therefore be used to identify the glycerol position of an unsaturated fatty acid in the triacylglycerol molecule (89).…”
Section: 89mentioning
confidence: 99%